A model to characterize the lateral expansion of a cylinder containing a polymer filler subjected to compression. Issue 1 (2nd January 2021) - Xu, Lizhi; Gao, Guangfa; Wang, Xiaodong; Wang, Jiangbo; Chen, Xi
Abstract: This article presents a model to characterize the lateral expansion of metal cylinder expanded by polymer filler and analyzes the influencing factors to the expansion. Based on the elastoplastic theory of thick-walled cylinder and the Drucker–Prager yield criterion, the expansion model which considers the material properties and dimensions of the filler and the cylindrical shell is constructed. To verify the accuracy of the model, a series of experiments, compared with the model, are conducted under different conditions (different materials of the filler, different thickness, and materials of the cylindrical shell), which illustrates that the proposed model is able to capture the response observed in experimental tests. Meanwhile, it is demonstrated that the relationship between axial stress and radial strain of the expansive specimen is mainly determined by the properties of the cylindrical shell instead of those of the filler, and the expansion decreases with the growth of the hydrostatic pressure.